Young stellar disks formed by the collision of a molecular cloud with a circumnuclear disk at the Galactic center. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Alig, C.; Schartmann, M.; Burkert, A.; Dolag, K.
Abstract: We suggest a new formation mechanism for the inclined, sub-parsec scale and counterrotating stellar disks observed around the central black hole in the Milky Way Galactic center. The simulation of a single molecular cloud crashing into a circumnuclear ring of gas leads to the inflow of multiple streams of gas towards the central parsec region. The time delayed arrival of those streams forms multiple, sub-parsec scale accretion disks, with angular momentum depending on the ratio of cloud and circumnuclear ring material. These accretion disks could then be the progenitors which fragmented into the observed stellar disks. A similar event might have also led to the creation of the so-called minispiral in the Galactic center.